1988
DOI: 10.1016/0003-9861(88)90064-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol feeding on hepatic lipid synthesis

Abstract: Rats were fed a high-fat, liquid diet containing either 36% of total calories as ethanol or an isocaloric amount of sucrose, for a period up to 35 days. At different time intervals we measured the effects of ethanol administration on the activities of a number of key enzymes involved in hepatic lipid synthesis. At the start of the experimental period the activities of acetyl-CoA carboxylase and fatty acid synthase, measured in liver homogenates, increased in the control as well as in the ethanol-fed group. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…in vivo measures of DNL and concluded that increases in this pathway are not a major contributor to the development of alcoholic steatosis ( 29,30 ). Although it was not the focus of our follow-up studies, we would highlight that the literature regarding alcohol's effect on the function of PPAR ␣ is also equivocal.…”
Section: Discussionmentioning
confidence: 91%
“…in vivo measures of DNL and concluded that increases in this pathway are not a major contributor to the development of alcoholic steatosis ( 29,30 ). Although it was not the focus of our follow-up studies, we would highlight that the literature regarding alcohol's effect on the function of PPAR ␣ is also equivocal.…”
Section: Discussionmentioning
confidence: 91%
“…The samples were evaporated to dryness at room temperature and transferred to scintillation vials for reading. Enzyme activity was expressed as [1-14 C]bicarbonate incorporation into FA min −1 mg protein −1 (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…and the correlation of the ACP phenotypes in different tissues. This hy pothesis is supported by the low level of en zyme activity of the ACP AC phenotype [32], and by the role suggested for ACP in the bio synthesis of the fatty acids, and in the metabo lism of the ethanol [33][34][35].…”
Section: Discussionmentioning
confidence: 95%